Impacts of soil‐borne disease on plant yield and farm profit in dairying soils. Issue 1 (9th December 2021) - Dignam, Bryony E. A.; Marshall, Sean D. G.; Wall, Andrew J.; Mtandavari, Yeukai F.; Gerard, Emily M.; Hicks, Emily; Cameron, Catherine; Aalders, Lee T.; Shi, Shengjing; Bell, Nigel L.
Abstract: Introduction: Globally, soil‐borne plant pathogens are a significant contributor to plant yield loss in agricultural systems, including pasture production. The extent of soil biological constraints in high‐value dairy systems was assessed across three major dairying regions of New Zealand. Materials and Methods: Regional measures of disease pressure were obtained by comparing white clover, perennial ryegrass and plantain growth in 30 farm soils with (non‐pasteurised) or without (microwave pasteurised) their normal complement of microbial and nematode pathogens. Results: Pasteurising soils from the Waikato region led to significant average increases in clover (35%) and ryegrass (19%) shoot dry matter. Individual site yields increased up to 74% for clover and 38% for ryegrass. For Canterbury and Southland, there was no increase in plant yield with pasteurisation on a regional basis, but increases in either clover or ryegrass were significant at three individual farm sites. Across all regions, negative linear relationships between disease pressure (% growth change) and a proxy of soil organic matter quality (anaerobically mineralizable nitrogen:total nitrogen ratio were found for both clover and ryegrass, accounting for 34% of the variation in both clover and ryegrass growth. A positive linear relationship was found between disease pressure and Heterodera cyst nematode abundance, accounting for 33% and 17% of the variation in clover and ryegrass growth change, respectively. The most prevalent putative fungal and oomycete pathogens isolated from the roots and stem bases of clover and ryegrass seedlings were Fusarium oxysporum, Fusarium culmorum, and various Pythium species. Conclusion: Our results suggest that root pathogens on New Zeland dairy farms are most prevalent and damaging in the Waikato region where economic modelling estimated clover and ryegrass root disease to cost 211 kg MS ha −1 year −1 in milk production and $909 ha −1 year −1 in farm profitability. Given the scale of these costs, targeted management of soil borne disease could present an economically viable approach to improving the resilience of these multi‐plant multi‐pathogen ecosystems.